Anti-Gal IgM, IgA and IgG natural antibodies in childhood - Hamanova, Marketa; Chmelikova, Magda; Nentwich, Ivo; Thon, Vojtech; Lokaj, Jindrich (Immunology letters, 2015)
The target for the most abundant xenoreactive natural antibodies in humans is the α-Gal epitope. Anti-Gal could provide natural immune defense against pathogens that express the α-Gal epitope. Anti-Gal natural antibodies are usually studied in adult individuals. Data demonstrating the incidence and concentration of anti-Gal natural antibodies in childhood are in short supply and incomplete. In the present study we prospectively quantified anti-Gal IgM, IgA and IgG levels in different age groups of children from delivery to 24 months of age and compared these levels to the level of these antibodies in their respective mothers. Measurement of anti-Gal antibodies may broaden the spectrum of specific antibodies that are available for determination of specific antibody responses in physiological and pathological conditions in children. Plasma was collected from umbilical cord blood of full term newborn, from blood of infants at age 6, 12 and 24 months and from their respective mothers at time of delivery. Quantitative determination of anti-Gal antibodies IgM, IgA and IgG were made with the enzyme immunoassays Human Anti-Alpha Galactosyl IgM ELISA, IgG ELISA and IgA ELISA. Hemagglutination activity was titrated against rabbit erythrocytes. The kinetic processes for the formation of natural antibodies in the first two years of life, in general, compared with the kinetics for the formation of total immunoglobulins IgM, IgA and IgG. There were no detectable anti-Gal IgM and IgA in the cord blood, whereas anti-Gal IgG were found at similar levels in both neonate cord blood and peripheral blood of their respective mothers. When comparing the percentage of natural antibodies in the plasma of children, the level of natural antibodies in children at the age of two years was approximately 37% for IgM, 25% for IgG and 15% for IgA. The titration of antibodies required for agglutination of rabbit red blood cells over the 24 month period followed the same trend observed for the formation of natural antibodies. Our study demonstrates the kinetics of formation of anti-Gal IgM, IgA and IgG natural antibodies in the first two years of life. The relative lack of these antibodies in this period should be taken into account when assessing for humoral immunodeficiencies, particularly with regards to the potential for children to mount an anti-carbohydrate response.
Keywords: novorozenec; Infant, Newborn; Immunodeficiency; Infant; Humans; kojenec; imunoglobulin G; trisacharidy; věkové faktory; Childhood; Natural antibodies; lidé; Trisaccharides; Immunoglobulin A; předškolní dítě; Kinetics; Anti-Gal; imunoglobulin A; imunoglobulin M; Age Factors; Immunoglobulin G; Child, Preschool; Immunoglobulin M